On a Conversation between Socrates and Meno in the Dialogue Meno - 10.33112/nm.15.1.32 (Nordicum-Mediterraneum, 2020)
This short text discusses Part II of Plato’s dialogue Meno, in which Socrates asks the boy to construct a square twice the area of a given square. Socrates presupposes that the boy already knows what a square looks like (“what it is” in everyday language), knows (accepts) that the four sides of the square are equal and that two are parallel to the base, two to the vertical. the boy sees a figure that he has learnt is called “a square”. When a “diagonal” is added he sees it. When he is told that the diagonal is the length of the lines in a square twice the area he may believe that to be the case but he does not yet know. When he discovers that to be so he sees no more than before; but understands and knows. What he understands is the form of a square. His movement from seeing to questioning, to understanding and knowing is, perhaps, not unlike that of those in the cave in the Republic.